Changes of pro- inflammatory and anti-inflammatory interleukins in cases of implantation of polypropylene meshes of different types in implant hernioplasty - Piatnochka, V. I.; Herasimets, Y. M.; Svistun, R. V.; Polyatsko, K. G.; Prodan, A. M. (Journal of Education, Health and Sport, 2018)
The use of polypropylene meshes in the treatment of ventral and postoperative ventral hernias is uncontroversial. Their use is accompanied by a significant inflammatory response in the implantation area, contributes to the formation of a dense connective tissue capsule and, as a result, leads to shrinkage of the mesh. The issue of postoperative exudative complications that complicate the postoperative course much is topical. Objective. The aim of the research was to conduct a comparative evaluation of the results of the use of ‘light’, ‘heavy’ polypropylene meshes, as well as the ‘light’ one in combination with the PRF membrane, based on the study of the state of systemic indices of cytokines in retro-muscular allohernioplasty in the patients with primary and postoperative ventral hernia. Materials and methods. The research was based on the examination of 165 patients, who underwent surgery for primary and postoperative ventral hernia with the implantation of ‘light’, ‘heavy’ polypropylene meshes, as well as the ‘light’ one in combination with the PRF membrane. The study of systemic indices of cytokines in the serum of peripheral blood were conducted. The ratio of pro-inflammatory and anti-inflammatory interleukins TNF-α, IL-8 and IL-4 as well as the content of serum immunoglobulin (Ig) A was determined before the surgery, on the first day after the surgery, and on the day of discharge from the hospital (7-9th day of the postoperative period), in order to evaluate the stage and course of the immune response to the implantation of different types of polypropylene meshes. Results. On the day of discharge from the hospital, a decrease in the level of pro-inflammatory and anti-inflammatory cytokines in the main group was evidenced in the patients, who underwent implantation of the ‘light’ mesh as well as in those, who underwent implantation of the ‘light’ one in combination with the PRF membrane. In the patients, who underwent ‘heavy’ mesh implantation, a statistically significant increase in IL-8 and IL-4 levels was proved on the day of discharge from the hospital (p<0.05). A decrease in the level of total and secretory IgA in the main group of patients, who underwent implantation of the ‘light’ mesh in combination with the PRF membrane, was evidenced, though in the patients, who underwent implantation of the ‘light’ mesh, the indices did not change compare to the 1st postoperative day. In the patients, who underwent implantation of the ‘heavy’ mesh, a statistically significant increase in both total and secretory IgA levels was proved on the day of discharge from the hospital (p<0.05). Conclusions. In the patients with primary and postoperative ventral hernia in cases of implantation of a ‘heavy’ polypropylene mesh, the immune response was characterized by a significant intensification of local and overall immune defense (according to the content of Ig A), and increase in pro-inflammatory and anti-inflammatory cytokines. When using the ‘light’ meshes in combination with the PRF membrane in the patients with primary and postoperative ventral hernia, the state of immune status was the best compared to the baseline data: the number of pro-inflammatory and anti-inflammatory interleukins decreased, local and overall immune defense reduced.